PORTABLE SOIL-FILLED BARRIER FOR BLAST MITIGATION APPLICATIONS - Jestin Jelani (Thesis, 2019)
In this research, a Portable Soil-filled Barrier (PSB) is developed to improve the soil barrier performance in mitigating blast overpressure as well as construction techniques. Numerical simulation model using AUTODYN3D is developed to investigate effective shapes and orientations of soil barrier in mitigating blast wave.